Financial Performance Analysis of PT Astra International - Eko Agus Setiawan; Riskin Hidayat; Sri Hermuningsih (Universitas Teknokrat Indonesia, 2025)
This study evaluates PT Astra International Tbk (Astra) 's financial performance for 2019-2023 using financial ratios from five dimensions: liquidity, capital structure, profitability, return on investment, and financial market size. The liquidity dimension is analyzed through current, quick, and cash ratios. Capital structure is evaluated by the debt-equity ratio (DER) and debt-to-asset ratio (DAR). Profitability is measured by Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). Return on investment is analyzed using ROI and asset turnover ratio (ATR), while the financial market size is measured by P/E Ratio, P/BV, and dividend yield. The results show solid performance in profitability and return on investment despite challenges in liquidity. This research provides a comprehensive overview of Astra's financial performance and contribution to its competitiveness.